2016
DOI: 10.1614/ws-d-15-00068.1
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking Outreach: Collaboration Is Key for Herbicide-Resistance Management

Abstract: Effective outreach is critical to achieving success in managing herbicide-resistant weeds. Interdisciplinary collaboration is needed to adapt information delivery and to engage communities to address the herbicide-resistance problem. Weed scientists must partner with the production community to adapt herbicide-resistance practices for local needs, to work collaboratively with state and regional stakeholders to create effective resistance-management practices, and to provide an overarching national message as t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 23 publications
(31 reference statements)
2
8
0
Order By: Relevance
“…More emphasis on integrating the human and social dimensions of IWM is required. This requires input from social science disciplines, such as economists and social psychologists …”
Section: Seven Point Action Plan To Improve Uptake Of Iwmmentioning
confidence: 99%
“…More emphasis on integrating the human and social dimensions of IWM is required. This requires input from social science disciplines, such as economists and social psychologists …”
Section: Seven Point Action Plan To Improve Uptake Of Iwmmentioning
confidence: 99%
“…Nonetheless, these findings echo calls to have more collaboration across groups of influencers to provide a clear and consistent message to farmers regarding herbicide resistance and weed management tactics (Asmus and Schroeder 2016; Barrett et al 2016; Coble and Schroeder 2016; Hurley and Frisvold 2016). In a recent report of listening sessions with various agricultural stakeholders across regions of the United States, participants from the Midwest, Northeast, and Southeast said they wanted more education and collaborative communication for managing herbicide resistance (Schroeder et al 2018).…”
Section: Resultsmentioning
confidence: 84%
“…Previous research has shown that often the most influential source of weed management information is the agricultural input network of chemical, seed, and equipment manufacturing companies, distributors, and retail outlets (Coble and Schroeder 2016;Givens et al 2011;Johnson et al 2009), which was also evident in our surveys. Arbuckle (2014) reported that 78% of farmers in Iowa relied on their agricultural chemical retailer for advice on weed management decisions. Contrary to this hierarchy, a survey distributed in Iowa, Illinois, Indiana, Mississippi, North Carolina, and Nebraska asking where growers receive their information on glyphosate resistance indicated that more than 50% of respondents in each state received information from farm publications.…”
Section: Source Of Informationmentioning
confidence: 99%
“…Many respondents were not relying on Extension directly as an information source, yet they were not relying much on any other single alternative source either. Asmus and Schroeder (2016) discuss similar results regarding Extension and weed management for agronomic crops, whereas Frisvold and Deva (2012) report similar results for Extension and irrigation management. The survey results suggest there is no “one-stop shopping” for annual bluegrass management information.…”
Section: Resultsmentioning
confidence: 90%